ASSET BASED COMMUNITY DEVELOPMENT DI PESANTREN WISATA: IMPLEMENTASI STRATEGIS DI PP. AN-NUR 2 AL MURTADLO MALANG - Djawahir, Abdillah Ubaidi (Jurnal Pengabdian Kepada Masyarakat, 2018)
This paper aims to explore the Asset Base Community Development (ABCD) on the implementation of the pesantren community, focusing on seven specific principles. Induction deduction design, including in-depth interviews, Focus Group Discussion (FGD), workshops, observations, and document analysis, were used. Findings of "Mapping Tourism Asset" Pesantren Wisata Annur 2 Al Murtadlo Malang. Community members have a high level of shared meaning, commitment, full participation and an internationally focused democratic power distribution, social capital ties, and effective access to internal resources. And good relationships with communities and external organizations. Pesantren as an institution has both material and immaterial tools. Both are the components of the existence of pesantren as an institution of education, social and religious. The Mapping Tourism Asset becomes a strong marker for the development of pesantren from an institution of religious education (Islam), socially, culturally and culturally has a strong opportunity to become part of the growth the halal tourism industry in Indonesia. The approach and methodology of ABCD used in this research resulted in mapping "tourism assets" of pesantren wisata that is, the true of education program; museum; spot of selfie; bank of garbage; and the souvenir center.